Transfer of Green Fluorescent Protein (GFP) Gene to Betta splendens Embryos by Transfection and Electroporation Methods - Eni Kusrini; Alimuddin Alimuddin; Erma Primanita Hayuningtyas; Syuhada Restu Danupratama (Journal Omni-Akuatika)
Transfection and electroporation method shave a high possibility to apply towards transgenic production of small eggs size fish species.  This study aimed to examine the potential of transfection and electroporation methods to use for transferring a foreign gene into betta fish (Betta splendens) embryos using green fluorescent protein (GFP) gene as a model.  Fish were spawned naturally in the ratio of male: female was 1:1, then a total of 200 eggs were taken for each treatment.  Transfection was performed for 30 minutes (room temperature of about 25 °C) at two-cell stage of embryos using transfast reagent.  Transfection reaction consisted of 0.75 µL transfast reagent, 0.25 µL GFP expression vector (DNA concentration: 50 µg/µL) and 99 µL NaCl solution (concentration: 0,95%).  Electroporation was performed using 125 volt cm-1, 3 times pulse frequency at one second interval and pulse length of 7 micro seconds.  A volume of 800 µL GFP expression vector solution (DNA concentration: 50 µg/ µL) in PBS was used for electroporation.  The successful of foreign gene transfer was determined by PCR method with GFP specific primers.  The results showed that hatching rate of eggs in transfection treatment was 67.08%, while the electroporation was 72.09%.  Survival of larvae in transfection treatment was 73.00%, while the electroporation was 75.00%.  The results of PCR analysis showed that transfection method allowed 65% of the survived fish carrying GFP gene, whereas the electroporation method was 70%.  Thus, foreign gene transfer in betta fish can be conducted using the transfection and electroporation methods.